PEMANFAATAN BATANG PISANG SEBAGAI PAKAN TERNAK - Moh.Azus Shony Azar; Ahmad Fathur Rozi; Ahmad Ahsanul Falih; Ahmad Faizal Reza (LPPM Universitas Islam Darul 'Ulum Lamongan, 2022)
A Banana waste is a problem faced by banana farmers or entrepreneurs who are widely scattered in banana-producing areas such as in Ds.Sumberaji, Kec. Sukodadi, Kab. Lamongan and if left unchecked, it has the potential to pollute the environment which can damage ecosystems in the area. . By applying fermentation technology that uses probiotics, the initially low nutritional value becomes very high nutritional value after fermentation. Thus, it can be concluded that the banana stem waste was originally only a waste, but it has the opportunity to be used as one of the raw materials for animal feed